Can Trait Mindfulness Improve Job Satisfaction? The Relationship Between Trait Mindfulness and Job Satisfaction of Preschool Teachers: The Sequential Mediating Effect of Basic Psychological Needs and Positive Emotions - Song, Zhanmei; Pan, Baocheng; Wang, Youli (Frontiers in Psychology, 2021)
Objective: This study aims to explore the relationship between basic psychological needs and positive emotions of preschool teachers between trait mindfulness and job satisfaction. Methods: 456 preschool teachers were tested with mindfulness attention awareness scale, basic psychological needs scale, positive emotion scale and job satisfaction scale. Results: Preschool Teachers trait mindfulness can predict job satisfaction. Preschool teachers trait mindfulness has an indirect impact on job satisfaction through basic psychological needs, and preschool teachers trait mindfulness has an indirect impact on job satisfaction through positive emotions. In addition, basic psychological needs and positive emotions play a sequential intermediary role between preschool teachers trait mindfulness and job satisfaction. Conclusion: Basic psychological needs and positive emotions play a sequential mediating role between preschool teachers trait mindfulness and job satisfaction, and this sequential mediating effect accounts for a high proportion of the total effect.